Analisis Kesalahan Penggunaan Konjungsi Bahasa Jerman Pada Karangan Sederhana - Taqiyuddin, Muhammad Fikri; Hasmawati, Hasmawati; Burhanuddin, Burhanuddin (Academic : Journal of Social and Educational Studies, 2022)
Abstract. This research is a type of descriptive research with a qualitative approach, this study aims to determine the forms of mistakes in using German conjunctions and the factors that influence students' mistakes in using German conjunctions. Subject in this research were 19 XII language students at MAN 1 Palu city, and object in this study was a collection of data on errors in German conjunction use and the factors that drive errors in conjunction use. The research method in this study is the listening method with an advanced technique, namely the note-taking technique using the analytical step of Tarigan (2011:16). Based on the results of data analysis from tests and distributed questionnaires, 23 mistakes in using conjunctions were identified by the students, and the types of mistakes were classified into 4 types of mistakes, which divided the factors that caused students to make mistakes in using German conjunctions into internal factors and external factors with 4 students writing down factors with the difficult to understand German conjunctions being the largest factor.  Keywords: Error Analysis Of Conjunction Usage, Analysis Results, Error Factors